Occasional phraseological units in modern Ukrainian prose (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The individual-author’s (occasional) transformations of units of phraseological linguistic level used in texts of modern Ukrainian prose, particularly in M.Matios’s, Y.Andruhovych’s and others’ compositions, are described in the article.
Keywords: occasional transformation; usage (occasional) phraseological unit; stylistic effect